A Dietary Supplementation with Leucine and Antioxidants Is Capable to Accelerate Muscle Mass Recovery after Immobilization in Adult Rats - Savary-Auzeloux, Isabelle (Public Library of Science, 2013)
Prolonged inactivity induces muscle loss due to an activation of proteolysis and decreased protein synthesis; the latter is also involved in the recovery of muscle mass. The aim of the present work was to explore the evolution of muscle mass and protein metabolism during immobilization and recovery and assess the effect of a nutritional strategy for counteracting muscle loss and facilitating recovery. Adult rats (6–8 months) were subjected to unilateral hindlimb casting for 8 days (I0–I8) and then permitted to recover for 10 to 40 days (R10–R40). They were fed a Control or Experimental diet supplemented with antioxidants/polyphenols (AOX) (I0 to I8), AOX and leucine (AOX + LEU) (I8 to R15) and LEU alone (R15 to R40). Muscle mass, absolute protein synthesis rate and proteasome activities were measured in gastrocnemius muscle in casted and non-casted legs in post prandial (PP) and post absorptive (PA) states at each time point. Immobilized gastrocnemius protein content was similarly reduced (-37%) in both diets compared to the non-casted leg. Muscle mass recovery was accelerated by the AOX and LEU supplementation (+6% AOX+LEU vs. Control, P<0.05 at R40) due to a higher protein synthesis both in PA and PP states (+23% and 31% respectively, Experimental vs. Control diets, P<0.05, R40) without difference in trypsin- and chymotrypsin-like activities between diets. Thus, this nutritional supplementation accelerated the recovery of muscle mass via a stimulation of protein synthesis throughout the entire day (in the PP and PA states) and could be a promising strategy to be tested during recovery from bed rest in humans.